Effect of Ethanol in Oral Antiseptic Sprays on Breath Alcohol Measurement - Demirci, İsmail Mehmet and Balcı, Yasemin and Kadı, Gülsüm and Seçkin, Çetin and Tosun, Kürşad (The Bulletin of Legal Medicine, 2021)
Objective:Breath alcohol concentration (BrAC), in routine traffic control, might be higher due to reasons which effect mouth alcohol concentration. According to Highways Traffic Regulation, there is no possibility to remeasure with technical device, in case of any objection.In this study, we aimed to answer firstly how oral antiseptic sprays effect BrAC and then what correlation between BrACs and time is. Material and Method:This study included 30 healthy volunteers’ results. In this study, three oral antiseptic sprays (OAS) which contain ethanol and electrochemical breathalyzer are used. BrAC(Tbefore)before spray use, was taken as the reference value for each subject.Subjects sprayed 3 puffs of OAS into their mouths.Following 3 puffs, the subjects kept their mouths closed and immediately underwent a breathalyzer examination to evaluate BrAC(T0).Two more examinations were conducted 3 minutes later(T3) and 5 minutes later(T5) without any use of the sprays. Results:The highest BrAC value(4.25permille) was attained at T0 in 12 subjects; all BrAC values(before spray use) were negligible and under 0.08 permille.The BrAC median values decreased under legal limit zero as time passed by from T0 to T3 and T5.T3 values were lower than the T0 values for all OASs and all T5 values were lower than T0 and T3 values. Conclusıons:This research study shows that OASs may alter the results of a single breathalyzer test. Based on our results, BrAC values are effected by ethanol in the oral cavity due to prior use of OAS and this explains why BrAC decrease rate is really remarkable. KeyWords:Breath alcohol level,Oral antiseptic sprays,Breathalyzer.